578 Is the Scope of the Physician's Duty to Warn the Patient About the Risks Associated with a Surgery Sufficiently Clear?. (19th August 2022) - Kazzazi, F; Noton, T; Magill, H
Abstract: Aim: To critically analyze the concepts and cases that led to the seminal rulings in Montgomery and Sidaway Method: A medical and legal literature review was performed. Case history was identified and critically analysed to understand the progression of consent law in England. Results: The physician's duty to warn the patient about the risk associated with medical intervention has been developed through the cases identified to involve: Information-giving of the procedure and its process Information regarding potential alternatives and their comparative risks Respond to patient questions (except in times of possible psychological harm) Disclosure of risks that any reasonable patient wishes to know Disclosure of "material risks" that are pertinent to the specific patient The process of consent is of chief importance in surgery and yet only a single case ( Chester ) directly involves consenting during a surgical procedure. Conclusion: The definition of material risk is expected to cover a plethora of medical interventions from minor procedures to major surgery. It was generated predominantly from non-surgical cases. The physician's scope to disclose risks to patients is broad and encompasses a skillset that incites core clinical skills of empathy, honesty, and information transfer. It has evolved alongside advances in medical and legal judgement, albeit reactively to cases of inadequate care. With regard to its clarity, one has to consider the acceptable boundary of prescriptivism that both respects patient autonomy and creates a transparent working environment. It can be argued that the current scope is not direct enough for healthcare professionals.